CAPOEIRA: A PHYSICAL AND SPIRITUAL ART OF CORPORAL CARE (Fiep Bulletin - online, 2012)
In this paper we argue that capoeira as a cultural expression of African origin has the potential to promote the integral development of students, meeting the goals set by the National Curriculum Parameters (NCP) for Physical Education. We justify our argument by providing a brief history and main features of capoeira, which combines music, movement and spirituality as a way to fulfill individuals' needs. We remark that prejudice can not shadow the contribution of capoeira to promote creativity, attention, self-esteem, and psychosocial equilibrium, all essential to the exercise of citizenship. We conclude defending the inclusion of capoeira in the curriculum to meet the Law of Guidelines and Bases of National Education, which determines that our African cultural heritage must be taught through interdisciplinary approaches in elementary and middle school. We conclude that contact with such practices puts in the horizon of possibilities for teaching and learning the denaturalization of stigmas attached to Brazilian culture, as well as elements to overcome the prejudices regarding contributions coming from the African-Brazilian universe.
Keywords: Capoeira; Physical Education; Corporeality